2012
DOI: 10.1134/s0032945212010079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the long-term anosmia combined with vision deprivation on the taste sensitivity and feeding behavior of the rainbow trout Parasalmo (=Oncorhynchus) mykiss

Abstract: We compared taste preferences, taste sensitivity, and behavior in testing food objects in the group of intact and two groups of sensory deprived rainbow trout Oncorhynchus mykiss yearlings. We demonstrated that long term anosmia (for 9 months), as well as anosmia (for 9 months) combined with enucleation (object vision deprivation for 4 months), does not change the taste preference of fish for the agar pellets containing amino acids (L alanine, L proline, L histidine, or glycine; 0.1 M). For all groups of fish,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The fish originally fed the carnivorous diet showed a palatability 1.27 and 1.07 times greater for pellets flavoured with chironomids ( P < 0.001 for both) and fish originally fed the herbivorous diet showed a palatability of 1.22 ( P < 0.01) and 0.99 ( P > 0.05) times greater for pellets flavoured with duck weed and lettuce, in a series of two behavioural trials (Kasumyan & Morsi, ). The differences were not related to the smell of pellets because the response of fish to flavoured pellets is not mediated by olfaction (Kasumyan & Sidorov, ).…”
Section: The Effects Of Environmental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish originally fed the carnivorous diet showed a palatability 1.27 and 1.07 times greater for pellets flavoured with chironomids ( P < 0.001 for both) and fish originally fed the herbivorous diet showed a palatability of 1.22 ( P < 0.01) and 0.99 ( P > 0.05) times greater for pellets flavoured with duck weed and lettuce, in a series of two behavioural trials (Kasumyan & Morsi, ). The differences were not related to the smell of pellets because the response of fish to flavoured pellets is not mediated by olfaction (Kasumyan & Sidorov, ).…”
Section: The Effects Of Environmental Variablesmentioning
confidence: 99%
“…The evidence suggests that the extraoral taste system plays a main, if not the leading, role in such sensory plasticity. It was shown that this phenomenon is a common feature for fishes that possess extraoral taste buds normally, such as in the acipenserids and cyprinids, but was not found in fishes in which TB location is restricted to the oral cavity only, such as in salmonids, cichlids and characids (Kasumyan & Marusov, , ; Kasumyan & Sidorov, ; Marusov & Kasumyan, , ). Chronic anosmia leads to functional shifts in the external taste system, increases the external TB number and affects morphology and distribution, while no similar changes have been found for the intraoral taste buds (Devitsina & Marusov, ; Kasumyan, ).…”
Section: Phenotypic Compensatory Plasticitymentioning
confidence: 99%
“…However, there are interspecies differences in manifestation of stereotypes. For instance, three spined stickleback performs more cycles of graspretention-rejection at manifestation of food con sumption stereotype, which makes it closer to stone loach, but distinguishes it from common carp, rain bow trout, and roach (Kasumyan and Sidorov, 2010a, 2010b, 2012Kasumyan and Tin'kova, 2013). A small number of studied species does not allow us to formu late now any common interrelations between manifes tation of stereotypes and ecology of fish, their feeding mode, and other specific biological features.…”
Section: Discussionmentioning
confidence: 86%
“…It is suggested that selection of pattern according to which behavior will develop occurs in fish early-already at the first moments of the object's contact with intraoral recep tors (Kasumyan and Sidorov, 2010). Stereotypes can differ in different fish, but there is one peculiarity common for all still scarce studies of species: time spent on realization of the food consumption stereo type is several times greater than time spent on mani festation of food rejection stereotype (Kasumyan and Sidorov, 2010a, 2010b, 2012Kasumyan and Tin'kova, 2013). It is possibly related to a more strict sensory control of food before swallowing.…”
Section: Discussionmentioning
confidence: 94%
“…Amino acids represent chemical signals in the gustatory system of fish, which are classified as inciting or stimulant and may differentiate the attractiveness of a feed. Among them, there can be highlighted: cysteine, betaine, glutamic acid, serine, glycine, alanine, proline, methionine, cysteine, phenylalanine, arginine, tyrosine, valine, leucine and glutamine (Kasumyan & Morsi, 1996;Kasumyan, 1997;Kasumyan & Doving, 2003;Hara, 2011;Suresh, Vasagam, & Nates, 2011;Kasumyan & Sidorov, 2012;Lokkeborg et al, 2014;Siikavuopio, James, Stenberg, Evensen, & Saether, 2017;Alves, Silva, et al, 2019;.…”
Section: Discussionmentioning
confidence: 99%